2011
DOI: 10.1063/1.3637629
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical expansion of the kinetic energy operator in curvilinear coordinates for the vibrational self-consistent field method

Abstract: A new hierarchical expansion of the kinetic energy operator in curvilinear coordinates is presented and modified vibrational self-consistent field (VSCF) equations are derived including all kinematic effects within the mean field approximation. The new concept for the kinetic energy operator is based on many-body expansions for all G matrix elements and its determinant. As a test application VSCF computations were performed on the H(2)O(2) molecule using an analytic potential (PCPSDE) and different hierarchica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 41 publications
0
29
0
Order By: Relevance
“…This success is entirely dependent on the use of the reaction path coordinate system. Other choices of coordinates would fare worse with this mean-field-based approach [19]. [35][36][37][38].…”
Section: Comparing Variational and Vmp2 Predictionsmentioning
confidence: 99%
See 1 more Smart Citation
“…This success is entirely dependent on the use of the reaction path coordinate system. Other choices of coordinates would fare worse with this mean-field-based approach [19]. [35][36][37][38].…”
Section: Comparing Variational and Vmp2 Predictionsmentioning
confidence: 99%
“…The semi-experimental structure requires theoretical input from rovibrational calculations, for which we turn to numerically exact variational methods. These results also serve as a useful reference for assessing the performance of approximate rovibrational methods, in particular curvilinear coordinate vibrational second order Møller-Plesset perturbation theory (VMP2) [17][18][19] and a recently developed extension for J > 0 rovibrational calculations [20]. The use of a curvilinear coordinate description makes this method applicable to molecules exhibiting large amplitude nuclear motion.…”
Section: Introductionmentioning
confidence: 99%
“…A lot of progress has been made developing methods for solving the nuclear vibrational Schrödinger equation, which have been described in some recent reviews . However, harmonic normal mode analysis remains the most widely used method for solving the nuclear vibrational Schrödinger equation.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that the local coordinates provide a Hamiltonian that is less coupled and beneficial in describing, for example, stretching vibrations of X-H (X=C, N, O) bonds, [27][28][29][30] the wagging of −NH 2 group, 31 the torsion of −OH group, [32][33][34][35] −CH 3 group, 36 etc. Although the curved motion of the internal coordinates gives rise to complex kinematic coupling in the kinetic energy operator, the techniques to automatically compute the kinetic energy terms have recently evolved.…”
Section: Introductionmentioning
confidence: 99%